Indigenous Boarding Schools and the Civilizing Project of the Franciscan Missions in the Peruvian Central Jungle (1840-1945) - Espinosa, Oscar (2025)
This article discusses the new evangelization and civilization strategy of the Franciscan missionaries for the indigenous peoples of the Peruvian Amazon at the end of the 19th and beginning of the 20th centuries. The text describes the historical context of the Peruvian Selva Central region as a frontier region, colonization area and a place marked by the violence of settlers and rubber entrepreneurs, which also involved child trafficking. It also details the situation of the Franciscan missions, the creation of boarding schools, and the inclusion, for the first time in history, of female missionaries in the educational and evangelizing processes led by the Catholic church in this region. Finally, it explains how the emphasis placed on boarding schools for indigenous children did not prevent the missions from collaborating on other tasks related to the colonization process promoted by the Peruvian State in the Amazon region.